PERANCANGAN APLIKASI E-GALERY - Nur avianto, Widhi; Agus Diartono, Dwi (Information Technology and Telematics, 2018)
Abstract - Art Gallery is a place where art lovers buy and order paintings, whether landscape paintings, face paintings and much more, and not infrequently this painting is usually used as a gift or just as a wall decoration. The purpose of this study was to create an Android-based painting ordering application. And the method used to build system development is the Waterfall method, then for the software used is Android Studio, and for the database using MySQ. From the results of research that has been done can be explained that the application has been built, the design of e-gallery applications, which are based on Android, is expected to facilitate users to process the painting order.